Removal of copper ions from contaminated aqueous solutions through adsorption process using modified polyurethane (PU) as an adsorbent - Saghi, Majid; Kaviani, Davood; Bagheri, Zahra; Padidaran, Behzad; Hosein Bigtan, Mohammad; Moghimi, Samira (Scientific Journal of Environmental Sciences, 2015)
Entering the pollutants specially heavy and toxic metals into the water resources has worried the human societies specially those researchers who have been studied much research about this field, this claim of which is proved by the number of valid published articles. Neglecting toxic material removing from water will pose the non-compensable injuries to living organisms and environment. In the paper, the 2- Mercaptobenzothiazole modified polyurethane foam has been used for removal of Cu ion from contaminated water solutions. The continuous experiments have been carried out through preparing adsorption columns for studying and optimizing the effect of primary concentration of the metal, pH, adsorbents used in respect of gram and various conditions for preparing the used polyurethane. The results of the experiments indicated that optimized condition for removing Cu ion with performance of includes 5 g modified polyurethane sorbent by modifier with concentration 0.001 M and pH=5.